Differences Of Reasoning Ability And Mathematical Representation Using Jigsaw Learning And Student Facilitator - Sari, Merisa Ammelia (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine the differences in the reasoning abilities and mathematical representation abilities of students who are taught using Jigsaw learning and Student Facilitator and Explaining learning in class X SMA PAB 6 Helvetia TP. 2019-2020.This research is a type of quantitative research with a quasi-experimental type of research. The population is all students of class X SMA PAB 6 Helvetia TP. 2019-2020. The samples in this study were class X MIA-1 and class X MIA-2. The data analysis technique used normality test, homogeneity test and hypothesis test using analysis of variance (ANAVA). These findings show: 1)The reasoning ability and mathematical representation ability of students taught by Jigsaw learning are better than students taught by Student Facilitator and Explaining learning, 2)Mathematical reasoning abilities of students taught by Jigsaw learning are not better than students taught by by learning Student Facilitator and Explaining, 3)The ability of mathematical representation of students who are taught by learning Jigsaw is better than students taught by learning of Student Facilitator and Explaining, 4)There is no significant interaction between the learning model used on reasoning ability and mathematical representation ability student.The conclusion of this study explains that the reasoning ability and mathematical representation ability of students taught by Jigsaw learning are better than students taught by Student Facilitator and Explaining learning in class X SMA PAB 6 Helvetia TP. 2019-2020.